Ranking Çanakkale Districts in terms of Rangeland Quality with Multi-Criteria Decision Making Methods - GÖKKUŞ, Zeynep; ŞENTÜRK, Sevil; ALATÜRK, Firat (Turk Tarim ve Doga Bilimleri Dergisi, 2023)
Based on the Project report of Determination of Rangeland Availability and Range of Rangeland Status Classes carried out by the Management of Eastern Anatolia Agricultural Research Institute, eleven districts of Çanakkale are ordered in terms of rangeland quality. For this reason, four different rankings were obtained by AHP, TOPSIS, VIKOR and WASPAS methods. According to the rankings made by the AHP, VIKOR and WASPAS methods, while the district with the highest rangeland quality was Biga, the highest rangeland quality according to the TOPSIS method was found to be the Central district.
Keywords: Agricultural Engineering (Other); Tarımsal deneylerde sıralama; AHP; TOPSIS; VIKOR; WASPAS.; Agricultural, Veterinary and Food Sciences; Ziraat Mühendisliği (Diğer); Ziraat, Veterinerlik ve Gıda Bilimleri; Ranking in agricultural experiments; AHP; TOPSIS; VIKOR; WASPAS; 2. Zero hunger; 15. Life on land